2001
DOI: 10.1080/13636820100200180
|View full text |Cite
|
Sign up to set email alerts
|

Learners and their workplaces: towards a strategic model of flexible delivery of training in the workplace

Abstract: Although the flexible delivery of training in the workplace has become a favoured policy position for training authorities in both Britain and Australia, this article reviews research that indicates neither learners nor their workplaces are well prepared. Drawing on the author's own research and that from the broader literature, the article develops a model for the preparation of learners and workplaces for flexible delivery of training. Deriving from the proposed model, the article suggests a wide range of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The all-time existence of LMS ensured the training of new employees with least efforts. In general, the learners and workplaces are not well prepared for training; therefore, we need to prepare them for flexible training delivery [35,47].…”
Section: Identification and Management Of The Challenging Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The all-time existence of LMS ensured the training of new employees with least efforts. In general, the learners and workplaces are not well prepared for training; therefore, we need to prepare them for flexible training delivery [35,47].…”
Section: Identification and Management Of The Challenging Dimensionsmentioning
confidence: 99%
“…The learners and their workplaces are often not well equipped to meet the demands of effective flexible delivery of training [34]. The learners should be motivated for self-directed learning with a minimum dependency on instructors [35]. Similarly, the workplace needs to be prepared by developing clear training policies, training structures, and trainers' development for supporting the learners [33,35,36].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2001) critiqued recent flexible learning initiativesin Australia and concluded that while on-line or internet based flexible learning packages can reap rewards, there are limitations, whereasSmith (2001), found "vocational learners are not typically self-directed, and prefer training in a structured and social environment, with guidance from instructors and peers" (p. 609) Lomine (2002). identified five myths of why hospitality and tourism teachers are reluctant to introduce online learning and teaching activities, andGillespie and Baum (2000) outlined best practice teaching methods which included the inclusion of an interactive CD-Rom in a food and beverage course.The integration of e-learning flexibility within hospitality studies has added new dynamism and reflects the industry's vitality.…”
mentioning
confidence: 96%
“…Industry personnel are proud of being part-time teachers in college. Part-time teachers usually work in the evenings [6]. High-level experts in the industry accept the invitation of Institute for regular or irregular technical presentations.…”
Section: Industry Participates In the Whole Process Of Tafe Collegesmentioning
confidence: 99%